Analysis of the Suitability of Pasarind Marketing Strategy with Customer Perception - Alza, Teuku Muhammad Fazhian; Linando, Jaya Addin (Research Horizon, 2025)
This study aims to identify customer perceptions of Pasarind and non-customer perceptions of Pasarind. This study uses a descriptive qualitative research method. The sample of this study consisted of six respondents consisting of three Pasarind customers and three non-customers. This study uses primary data collected by contacting respondents via telephone calls or WhatsApp to conduct interviews. The results of this study indicate that Pasarind users perceive the application as a functional POS (Point of Sales) system, providing benefits, having user-friendly features so that it is easy to use, and offered at an economical price. Non-customer perceptions of Pasarind include, first, Pasarind is less popular so that trust is reduced; second, less than optimal promotion so that marketing strategies cannot be achieved optimally; and third, strong competitors with advantages that require Pasarind to improve its quality in order to remain competitive in the POS industry. This study can be used by Pasarind to improve and optimize its marketing strategy, which ultimately strengthens its position in a changing and competitive market.